Commentary on the published position statement regarding the pathogenesis of fetal basal ganglia- thalamic hypoxic-ischaemic injury - J Anthony; J Smith; L Murray; G F Kirsten; G Gericke; Y Kara; V Davies; D Pearce; R van Toorn; M M Lippert; J W Lotz; S Andronikou; et al. (South African Medical Journal)
-